Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/molecules28083622
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Peroxide Activation Mechanism of Bimetallic MOF for Water Contaminant Degradation: A Review

Abstract: Metal–organic framework (MOF) materials possess a large specific surface area, high porosity, and atomically dispersed metal active sites, which confer excellent catalytic performance as peroxide (peroxodisulfate (PDS), peroxomonosulfate (PMS), and hydrogen peroxide (H2O2)) activation catalysts. However, the limited electron transfer characteristics and chemical stability of traditional monometallic MOFs restrict their catalytic performance and large-scale application in advanced oxidation reactions. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 111 publications
(131 reference statements)
0
5
0
Order By: Relevance
“…Advanced oxidation processes (AOPs) based on sulfate treatments have emerged as effective methods to remove pollutants from wastewater. 4,5 Owing to its asymmetric molecular structure and shorter O–O bond length, peroxymonosulfate (PMS, SO 5 2− ) is easier to activate than peroxydisulfate (PDS, S 2 O 8 2− ) and can generate a range of highly reactive substances, such as hydroxyl radicals (HO˙), sulfate radicals (SO 4 ˙ − ), superoxide radicals (O 2 ˙ − ) and singlet oxygen ( 1 O 2 ). 6–8 In addition, PMS offers several advantages for pollutant degradation, including high solubility, convenient transportation, and the ability to generate active substances over a broad pH range, leading to economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced oxidation processes (AOPs) based on sulfate treatments have emerged as effective methods to remove pollutants from wastewater. 4,5 Owing to its asymmetric molecular structure and shorter O–O bond length, peroxymonosulfate (PMS, SO 5 2− ) is easier to activate than peroxydisulfate (PDS, S 2 O 8 2− ) and can generate a range of highly reactive substances, such as hydroxyl radicals (HO˙), sulfate radicals (SO 4 ˙ − ), superoxide radicals (O 2 ˙ − ) and singlet oxygen ( 1 O 2 ). 6–8 In addition, PMS offers several advantages for pollutant degradation, including high solubility, convenient transportation, and the ability to generate active substances over a broad pH range, leading to economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Also, various metal–organic frameworks (MOFs) have been explored for catalyzing the oxidation of organic pollutants, activated by compounds like PDS, PMS, or H 2 O 2 . Bimetallic MOFs surpass single-metal ones, improving oxidation efficiency, catalytic activity, stability, and control in peroxide activation 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the advantages mentioned above, many studies have reported binary metal MOF-based nanomaterials with different compositions and structural properties that are widely used in environmental pollution control [24][25][26]. Fan et al [27] focused on the synthesis of bimetallic MOFs and catalytic degradation of water pollutants and further summarized in detail the influencing factors and catalytic mechanism of this material in the activation processes for peroxydisulfate (PDS), peroxymonosulfate (PMS), and peroxide (H 2 O 2 ). Soni et al [24] reported the latest developments in the synthesis and electrocatalytic activity of two-dimensional MOFs with bimetallic nodes.…”
Section: Introductionmentioning
confidence: 99%